Antimony recovery from copper refining electrolyte by membrane electrolysis - Belén Garrido; Javiera Lara; Juan Moreno; Alexandre Giacobbo; Eduardo Pino; Gerardo Cifuentes; Andréa Moura Bernardes (REM: International Engineering Journal)
Abstract To produce metallic copper with high quality, it is important to have all impurities present in the electrorefining cell under control. Antimony is present in the copper refining electrolyte as an impurity coming from pyrorefinated anodes. The antimony capture from the electrolyte is usually carried out by an ion exchange (IX) process. After that, an elution stage of Sb by means of a hydrochloric acid solution is accomplished, being the antimony eluate liquor sent for precipitation with gypsum and then landfilled. This article proposes an alternative to this classical antimony co-precipitation process, using a membrane electrolysis (ME) cell with a cation exchange membrane. This alternative route allows the recovery of metallic antimony at the ME cathode. ME experiments on lab scale were conducted to recover antimony as the cathode and using as an electrolyte, a real industrial hydrochloric eluate from the IX process. The ME tests were carried out with cathodes of stainless steel or cooper, at 200 and 300 A/m2, room temperature, without organic additives, and with different cell designs. The best results obtained were a stainless steel 316L cathode, faradaic efficiency of 92.46 % at current density of 200 A m-2, voltage 3 V and cathodic composition of Sb 75%. These results were obtained in a cell with the catholyte compartment closed at the top, showing the importance of the fluid-dynamic effect of the cell design on the Sb recovery.